1991
DOI: 10.2134/jeq1991.00472425002000020022x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemistry after Eleven Annual Applications of Cattle Feedlot Manure

Abstract: In a long‐term experiment at Lethbridge, AB, the effects of cattle (Bos sp.) manure on soil characteristics were determined after 11 annual applications. Manure, incorporated by cultivating, rototilling, or plowing, was applied annually from 1973 to 1983 at 30, 60, and 90 Mg ha−1 (wet wt.) and 60, 120, and 180 Mg ha−1, respectively, to nonirrigated and irrigated dark brown Chernozemic (Typic Haploborolls) clay loam soil. On both the nonirrigated and irrigated soil, the effects from manure, applied annually at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
5
7

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(164 citation statements)
references
References 0 publications
14
138
5
7
Order By: Relevance
“…Electrical conductivity, which is directly related to the salt concentration in the soil solution, has been shown to increase with increased compost application rates (Chang et al, 1991;Eghball, 2002). In our conditions, EC was not significantly affected whatever, the dose of applied compost.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Electrical conductivity, which is directly related to the salt concentration in the soil solution, has been shown to increase with increased compost application rates (Chang et al, 1991;Eghball, 2002). In our conditions, EC was not significantly affected whatever, the dose of applied compost.…”
Section: Discussionmentioning
confidence: 44%
“…Many other authors reported no effect on pH (Bevacqua and Mellano, 1994;Crecchio et al, 2001;Zebarth et al, 1999). However, there are several studies that revealed either an increase of acidic soil (Hue, 1992;Whalen et al, 2000;Baziramakenga et al, 2001;Butler and Muir, 2006;Valarini et al, 2009) or a decrease (Chang et al, 1991), While increasing pH is clearly valuable in terms of improving microelement availability, lowering pH should be limited to avoid enhancing the solubility of toxic elements. In this study, we did not detect Cd, Ni or Pb and most other heavy metals such as Cr, Zn, Mn, Ba, Sr and Ti were detected at very low concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have mostly compared the effects of increasing rates of fresh cattle manure on soil salinity and sodicity status (Wallingford et al 1975;Pratt 1984;Sweeten and Mathers 1985;Chang et al 1991;Davis et al 1997;Chang 2002, 2003;Olson et al 2003). However, we are unaware of any studies that have compared soil salinity and sodicity status of fresh and composted manure.…”
Section: Mots Clés: Sels Hydrosolubles Conductivité Ratio D'adsorptmentioning
confidence: 99%
“…Com relação às fontes orgânicas de nutrientes, a CA e o DLS não se diferenciaram em nenhum dos sistemas de manejo do solo, sendo que ambas apresentaram o maior risco ambiental (menor IRA), demonstrando que, mesmo nas doses utilizadas, que foram baseadas em estudos realizados com solos e culturas semelhantes aos utilizados neste experimento, houve risco ambiental com as doses aplicadas, sugerindo que o risco ambiental pode crescer com o aumento das doses de dejetos aplicadas, principalmente daqueles dejetos que apresentarem maiores concentrações de nutrientes. Neste sentido, Chang et al (1991) verificaram que o acúmulo de Zn, Mo, P total e disponível no solo aumentou com o aumento das taxas de dejeto bovino aplicado durante 11 anos. Adicionalmente, Ceretta et al (2005), em um trabalho com aplicação de doses de DLS em Argissolo Vermelho Distrófico arênico, verificaram que a recuperação de N, P e K pelas plantas atingiu o máximo até doses intermediárias, como 40 m 3 ha -1 , evidenciando que doses mais altas são menos eficientes à nutrição das plantas e potencializam os riscos de contaminação do solo e da água.…”
Section: Resultsunclassified
“…Dentre os elementos potencialmente poluidores, os metais pesados são importantes em virtude de se acumularem no solo e apresentarem possibilidade de inserção na cadeia alimentar (Muchovej & Obreza, 1996). Os dejetos também podem resultar na transmissão de patógenos, como as bactérias fecais e os protozoários no solo e na água (McMurry et al, 1998;Stoddard et al, 1998;Hunter et al, 2000), eutrofização das águas superficiais e contaminação do lençol freático por nitrato, entre outros (Chang et al, 1991;Bouchard et al, 1992;Angle et al, 1993;Moore Jr. et al, 1995;. A magnitude dos problemas ambientais devido ao uso dos dejetos também depende do preparo do solo utilizado (Angle et al, 1993;Stoddard et al, 1998).…”
Section: Introductionunclassified